Augmented Reality for Inclusive Physical Education: Development and Evaluation of Disability-Based Movement Adaptation Simulations - Merlina Sari; Novia Nazirun; Yoyon Efendi; Novri Gazali; Nagoor Meera Abdullah (Faculty of Sport and Health Sciences, 2026)
Adaptive physical education requires prospective teachers to have adaptive pedagogical competencies to respond to the diversity of students with disabilities. However, limited practical learning experiences in higher education often hinder students' understanding of movement adaptation. This study aims to develop and evaluate an augmented reality (AR) application as a simulation medium for movement adaptation based on disability types in adaptive physical education learning. A research and development approach was employed using the Multimedia Development Life Cycle (MDLC) model. The participants consisted of 30 physical education students selected purposively. The instruments included expert validation sheets, user practicality questionnaires, and movement adaptation comprehension tests. Data were analyzed descriptively and inferentially using a paired-sample t-test and effect size analysis. The results indicated that the AR application was valid (M = 4.28; 85.5%) and practical to use (M = 4.38; 87.5%). Furthermore, there was a significant improvement in students’ understanding of movement adaptation from pretest (M = 68.40, SD ≈ 6.00) to posttest (M = 82.60, SD ≈ 5.80), with a mean difference of 14.20 points. The improvement was statistically significant (p < 0.001) with a large effect size (Cohen’s d > 0.80). These findings demonstrate that the AR application is effective in enhancing students’ understanding of disability-based movement adaptation. Thus, the application has strong potential as an innovative learning medium to support the development of adaptive pedagogical competencies among prospective physical education teachers.